IDNLearn.com is designed to help you find reliable answers quickly and easily. Discover comprehensive answers from knowledgeable members of our community, covering a wide range of topics to meet all your informational needs.
Sagot :
Sure! Let's demonstrate that [tex]\((6 + 2 \sqrt{12})^2 = 12(7 + 4 \sqrt{3})\)[/tex] step by step.
### Step 1: Simplify the Expression Inside the Parentheses
First, look at the expression inside the parentheses on both sides.
For the left-hand side (LHS):
[tex]\[ 6 + 2 \sqrt{12} \][/tex]
We can simplify [tex]\(\sqrt{12}\)[/tex] since:
[tex]\[ \sqrt{12} = \sqrt{4 \cdot 3} = 2 \sqrt{3} \][/tex]
Thus,
[tex]\[ 6 + 2 \sqrt{12} = 6 + 2 \cdot 2 \sqrt{3} = 6 + 4 \sqrt{3} \][/tex]
Now our left-hand side expression becomes:
[tex]\[ (6 + 4 \sqrt{3})^2 \][/tex]
### Step 2: Expand the Squared Term on the Left-Hand Side
Next, we need to expand [tex]\((6 + 4 \sqrt{3})^2\)[/tex]:
[tex]\[ (6 + 4 \sqrt{3})^2 = 6^2 + 2 \cdot 6 \cdot 4 \sqrt{3} + (4 \sqrt{3})^2 \][/tex]
Calculating each term:
[tex]\[ 6^2 = 36 \][/tex]
[tex]\[ 2 \cdot 6 \cdot 4 \sqrt{3} = 48 \sqrt{3} \][/tex]
[tex]\[ (4 \sqrt{3})^2 = 16 \cdot 3 = 48 \][/tex]
So,
[tex]\[ (6 + 4 \sqrt{3})^2 = 36 + 48 \sqrt{3} + 48 \][/tex]
Combine the constant terms:
[tex]\[ 36 + 48 + 48 \sqrt{3} = 84 + 48 \sqrt{3} \][/tex]
Thus, the left-hand side becomes:
[tex]\[ (6 + 2 \sqrt{12})^2 = 84 + 48 \sqrt{3} \][/tex]
### Step 3: Simplify the Right-Hand Side
Now, let's simplify the right-hand side (RHS):
[tex]\[ 12(7 + 4 \sqrt{3}) \][/tex]
Distribute the 12:
[tex]\[ 12 \cdot 7 + 12 \cdot 4 \sqrt{3} = 84 + 48 \sqrt{3} \][/tex]
### Step 4: Equating Both Sides
We have:
[tex]\[ \text{LHS} = 84 + 48 \sqrt{3} \][/tex]
[tex]\[ \text{RHS} = 84 + 48 \sqrt{3} \][/tex]
Thus,
[tex]\((6 + 2 \sqrt{12})^2 = 12(7 + 4 \sqrt{3})\)[/tex].
This completes the proof.
### Step 1: Simplify the Expression Inside the Parentheses
First, look at the expression inside the parentheses on both sides.
For the left-hand side (LHS):
[tex]\[ 6 + 2 \sqrt{12} \][/tex]
We can simplify [tex]\(\sqrt{12}\)[/tex] since:
[tex]\[ \sqrt{12} = \sqrt{4 \cdot 3} = 2 \sqrt{3} \][/tex]
Thus,
[tex]\[ 6 + 2 \sqrt{12} = 6 + 2 \cdot 2 \sqrt{3} = 6 + 4 \sqrt{3} \][/tex]
Now our left-hand side expression becomes:
[tex]\[ (6 + 4 \sqrt{3})^2 \][/tex]
### Step 2: Expand the Squared Term on the Left-Hand Side
Next, we need to expand [tex]\((6 + 4 \sqrt{3})^2\)[/tex]:
[tex]\[ (6 + 4 \sqrt{3})^2 = 6^2 + 2 \cdot 6 \cdot 4 \sqrt{3} + (4 \sqrt{3})^2 \][/tex]
Calculating each term:
[tex]\[ 6^2 = 36 \][/tex]
[tex]\[ 2 \cdot 6 \cdot 4 \sqrt{3} = 48 \sqrt{3} \][/tex]
[tex]\[ (4 \sqrt{3})^2 = 16 \cdot 3 = 48 \][/tex]
So,
[tex]\[ (6 + 4 \sqrt{3})^2 = 36 + 48 \sqrt{3} + 48 \][/tex]
Combine the constant terms:
[tex]\[ 36 + 48 + 48 \sqrt{3} = 84 + 48 \sqrt{3} \][/tex]
Thus, the left-hand side becomes:
[tex]\[ (6 + 2 \sqrt{12})^2 = 84 + 48 \sqrt{3} \][/tex]
### Step 3: Simplify the Right-Hand Side
Now, let's simplify the right-hand side (RHS):
[tex]\[ 12(7 + 4 \sqrt{3}) \][/tex]
Distribute the 12:
[tex]\[ 12 \cdot 7 + 12 \cdot 4 \sqrt{3} = 84 + 48 \sqrt{3} \][/tex]
### Step 4: Equating Both Sides
We have:
[tex]\[ \text{LHS} = 84 + 48 \sqrt{3} \][/tex]
[tex]\[ \text{RHS} = 84 + 48 \sqrt{3} \][/tex]
Thus,
[tex]\((6 + 2 \sqrt{12})^2 = 12(7 + 4 \sqrt{3})\)[/tex].
This completes the proof.
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com is your source for precise answers. Thank you for visiting, and we look forward to helping you again soon.